(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
The uniqueness of the historical past of the Central Asian region, the history of relations between the peoples of Central Asia and China, as well as the significance of the processes taking place here for world history, increase the interest of researchers in them. This article analyzes sources related to relations between China and Central Asia.